Are children smoke‐free at home? Using wearable cameras to study children's exposure to smoking and smoking paraphernalia in private spaces. (12th December 2018) - Gurtner, Marcus; Gage, Ryan; Thomson, George; Jaine, Richard; Stanley, James; Smith, Moira; Barr, Michelle; Chambers, Tim; Signal, Louise
Abstract: Background: There is limited evidence available on the nature of children's exposure to smoking and smoking paraphernalia in private spaces (homes and cars). We aimed to evaluate the extent and nature of children's exposure to smoking in these settings using image data captured by wearable cameras. Methods: One‐hundred and sixty‐eight children wore wearable cameras for 4 days that automatically took pictures every 7 s. Images captured in private spaces ( n  = 140, 818) by children living in households with a smoker ( n  = 34) were screened for instances of smoking and smoking paraphernalia. Results: A total of 37 incidents of smoking—four indoor, 21 outdoor, and two in‐vehicles—and 62 incidents of smoking paraphernalia were observed. Most smoking incidents in homes (21 of 33) took place outdoors. Conclusions: The findings support health promotion efforts to make smokers more aware that smoking paraphernalia may normalize smoking for children. The methodology (wearable cameras) appears to have high utility for studying health behaviours in private spaces.